Correction to: Change in quality of life over eight years in a nationally representative sample of US adults with heart disease and type 2 diabetes: minority race and toxic stress as key social determinants - Allan K. Nkwata; Xiao Song; Ming Zhang; Amara. E. Ezeamama (BMC, 2020)
An amendment to this paper has been published and can be accessed via the original article.